Research of the Global Space Work Characteristic of Linear Delta Robot Versus Rotational Delta Robot - Yu Jin; Hu Bo; Liu Junhao; Liu Fuqiang (Jixie chuandong, 2020)
It is significant for Delta robot design to research on the work characteristics of the whole reachable workspace. The closed-loop vector equation is taken to solve the inverse kinematics of Delta robots， and vector expression of Jacobian matrix is deduced， the global stiffness index and the global dexterity index is established. The relationship between stiffness index and transmission angles of branched chains is obtained and verified， which make it possible to predict the stiffness performance by transmission angles. On the basis of the workspace and Jacobian matrix， the global stiffness index and the global dexterity index in the whole reachable workspace of two Delta robots with different configurations is obtained by Matlab， and the mechanism of the work characteristics difference between two kinds of Delta robots is researched. The conclusion shows that with the similar volume of reachable workspace， the stiffness of the linear Delta robot is superior to the rotational Delta robot， while the kinematics performance of the rotational Delta robot is better.